Improvement of liver metabolic activity in people with advanced HIV after antiretroviral therapy initiation. (1st October 2022) - Patel, Reema; Manion, Maura M.; Laidlaw, Elizabeth; Wakim, Paul; Wang, Zeping; Anderson, Megan; Galindo, Frances; Rupert, Adam; Lisco, Andrea; Heller, Theo; Sereti, Irini; Hammoud, Dima A.
Abstract : Objective: Evaluating hepatic metabolic changes in people with HIV (PWH) with advanced disease, before and after antiretroviral therapy (ART) initiation, using [ 18 F]-fluorodeoxyglucose (FDG) PET-computed tomography (PET/CT). FDG PET/CT noninvasively quantifies glucose metabolism in organs. Design/methods: Forty-eight viremic PWH (CD4 + cell counts <100 cells/μl) underwent FDG PET/CT at baseline and approximately 6 weeks after ART initiation (short-term). Twenty-seven PWH participants underwent follow-up scans 2 years after treatment (long-term). FDG PET/CT scans from 20 healthy controls were used for comparison. Liver FDG uptake was quantified from the PET/CT scans. Imaging findings as well as clinical, laboratory, and immune markers were compared longitudinally and cross-sectionally to healthy controls. Results: Liver FDG uptake was lower at baseline and short-term in PWH compared with controls ( P  < 0.0001). At the long-term scan, liver FDG uptake of PWH increased relative to baseline and short-term ( P  = 0.0083 and 0.0052) but remained lower than controls' values ( P  = 0.004). Changes in FDG uptake correlated negatively with levels of glucagon, myeloperoxidase, sCD14, and MCP-1 and positively with markers of recovery (BMI, albumin, and CD4 + cell counts) ( P  < 0.01). In multivariable analyses of PWH values across timepoints, BMI and glucagon were the best set of predictors for liver FDG uptake ( P  < 0.0001). Conclusion: Using FDG PET/CT, we found decreased liver glucose metabolism in PWH that could reflect hepatocytes/lymphocytes/myeloid cell loss and metabolic dysfunction because of inflammation. Although long-term ART seems to reverse many hepatic abnormalities, residual liver injury may still exist within 2 years of treatment initiation, especially in PWH who present with low nadir CD4 + cell counts.